An Fe-doped Co-oxide electrocatalyst synthesized through a post-modification method toward advanced water oxidation. Issue 8 (3rd February 2022) - Xu, Zhenhang; Zuo, Wei; Shi, Tianyu; Liu, Xinghai; Li, Houbin; Zhao, Pingping; Cheng, Gongzhen
Abstract : A new type of Fe-doped Co-oxide electrocatalyst Co3− x Fe x O4 -0.01 exhibited excellent OER activity at a current density of 10 mA cm −2 . The introduction of Fe not only successfully achieved the synergistic effect of CoFe, but also promoted the formation of oxygen bridges. Abstract : In the context of the ever-increasing energy crisis, electrocatalytic water splitting has attracted widespread attention as an effective means to provide clean energy. However, the oxygen evolution reaction (OER), which is an important anodic half reaction, shows very slow kinetics due to the multi-step electron transfer process, which severely restricts the efficiency of energy conversion. Herein, we used a simple solvothermal method to dope iron into the cobalt-containing hydroxide precursor, and successfully prepared the Fe-doped Co-oxide electrocatalyst Co3− x Fe x O4 -0.01. It only needs an overpotential of 294 mV to perform the OER at a current density of 10 mA cm −2, and has a low Tafel slope of 47.3 mV dec −1 . Moreover, Co3− x Fe x O4 -0.01 has excellent stability. There is no significant increase in the overpotential for oxygen evolution at a current density of 10 mA cm −2 after nearly 20 h. BET surface area test and XPS spectroscopy results show that Fe doping provides more mesopores and oxygen bridges, which is conducive to the construction of active sites and electronic regulation during the OER. This work can help design more bimetallic based highly active OER materials.